Biochemical association of regulatory variant of KLF14 genotype in the pathogenesis of cardiodiabetic patients - Alanazi, Abdullah Salah; Rasheed, Sumbal; Rehman, Kanwal; Mallhi, Tauqeer Hussain; Akash, Muhammad Sajid Hamid; Alotaibi, Nasser Hadal; Alzarea, Abdulaziz Ibrahim; Tanveer, Nida; Khan, Yusra Habib (Frontiers in Endocrinology, 2023)
Background and purpose: The study focuses on examining the relationship between a single nucleotide polymorphism in KLF14 rs4731702, and risk of T2DM and dyslipidemia in different ethnic populations. The purpose of this study was to evaluate the association between KLF14 rs4731702 and serum lipid profile and to determine the frequency distribution of KLF14 rs4731702 among T2DM and cardiometabolic patients. Methods: A total of 300 volunteers were recruited, consisting of three groups: 100 healthy individuals, 100 individuals diagnosed with T2DM, and 100 individuals diagnosed with cardiometabolic disorders. Biochemical analysis of blood samples was conducted to assess various biomarkers related to glycemic control and lipid profile. This involved measuring levels of glucose, TG, LDL-C, HDL-C, and ApoA1. Genotyping analysis was performed to investigate KLF14 polymorphism. The Tetra ARMS-PCR method was employed for genotyping analysis. Results: The results of biochemical profiling revealed a significant association between altered glycemic biomarkers and lipid profile in diseased patients compared to healthy participants. The frequencies of KLF14 rs4731702 alleles and genotypes were compared between the control group and T2DM group. A statistically significant difference was observed, indicating a potential association between KLF14 rs4731702 and T2DM. In the dominant inheritance model of KLF14 rs4731702 SNP, a statistically significant difference [odds ratio (95% confidence interval)] of 0.56 (0.34 – 0.96) was found between the control and T2DM subjects. This suggests that the presence of certain genotypes influences the risk of T2DM. In T2DM patients, individuals carrying the C allele exhibited compromised insulin sensitivity, decreased HDL-C and ApoA1 levels, and increased se-rum glucose, TG, and LDL-C concentrations. Conversely, TT genotype carriers demonstrated increased levels of HDL-C and ApoA1, lower insulin resistance, serum glucose, LDL-C, and TG levels. Conclusion: The study's findings indicate that dyslipidemia in T2DM patients is associated with reduced KLF14 functionality due to CC and CT genotypes, leading to insulin resistance and an increased risk of cardiovascular diseases. Additionally, risk of KLF14 rs4731702 polymorphism was found to increase with age and was more prevalent in fe-males than males. These insights contribute to understanding genetic factors influencing the development and progression of T2DM and dyslipidemia in different ethnic populations